Comparative Study of Dipteran Species Diversity and Their Succession on Rabbit Carrion in Two Different Mangrove Areas of Peninsular Malaysia. (21st August 2013) - Azmi, Wahizatul Afzan; Lim, S. P.
Abstract : A study on dipteran utility in assisting investigation of unattended deaths was carried out in mangrove areas of Kuala Terengganu, Terengganu, and Masai, Johor, in Peninsular Malaysia by using rabbit carrions as the model. The aim of this study was to determine the dipteran species diversity and their succession over the decomposition period of the rabbit carrions. A total of 229 individuals belonging to 11 species from six families of Diptera were successfully identified from both study sites in October and December 2007. Chrysomya megacephala, C. rufifacies, and Hydrotaea sp. were found to be the most abundant species recorded in this study. More species were collected from Masai with 10 species compared to Kuala Terengganu with nine species. Ecological indices (Shannon Wiener Index, Margalef Index, and Evenness Index) showed that Masai scored higher diversity, richness, and evenness values than Kuala Terengganu. However, Mann-WhitneyU test did not show significant difference among the individuals represented at each study site (P > 0.05 ). Calliphoridae predominated in the carrion during the fresh, bloat, and active decay stages of decomposition. Dipteran development was documented to be meteorologically dependent whereby; low temperature and high rainfall inhibit their colonization. Data collected in this study can hopefully serve as the basis for future estimates of the postmortem interval (PMI) particularly in mangrove area of tropical regions.